Thermal insulation properties of insulated concrete - Noor Fifinatasha, Shahedan; Mohd Mustafa Al Bakri, Abdullah; Norsuria, Mahmed; Kusbiantoro, Andri; Kamarudin, Hussin; Sandu, Andrei Victor; Naveed, M. (Syscom 18 SRL, 2019)
In building development, concrete is world most reliable, durable and versatile in construction materials. However, the heating and cooling system of the building is influenced by outside temperature due to extreme weather or areas condition leads to the consumption of a lot of electrical power. Thermally insulated concretes represent alternative construction materials to improve the thermal efficiency in building development. Various construction materials have different thermal insulation properties and thus, their suitability for various conditions vary. Thermal insulation properties are generally identified through specific heat, thermal conductivity, thermal diffusivity, thermal expansion, and mass loss. This paper present review the thermal insulation properties of variations insulated concrete are presently in growing demand of researchers to comfort and resolve prescribed issues related to insulated concrete in enhancing thermal insulation properties as a passive energy saving building.